Preparation method of dry-method electrode

By pulverizing and incorporating fibrilized materials at low temperature, the problem of waste of dry electrode tail material is solved, the reuse of electrode tail material and the maintenance of electrochemical properties is achieved, and the production cost is reduced.

CN119725399APending Publication Date: 2025-03-28CHINA LVFA INVESTMENT GRP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411948042.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When preparing dry electrodes, the tail material generated during the trimming and trimming of the self-support film causes 20% to 30% waste of material, increasing production costs.

Method used

The electrode tail material is crushed into powder by low-temperature crushing technology and mixed into the fibrillated material. After low-speed mixing, a mixed material is formed, and then a dry electrode is prepared by rolling and thermal composite.

Benefits of technology

The electrode tail material is effectively reused, which reduces production costs, and the electrochemical performance of the prepared dry electrode is less than 5% compared with the dry electrode prepared by pure fibrillated materials, which has better consistency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725399A_ABST
    Figure CN119725399A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a dry-method electrode, which comprises the following steps of: 1) crushing electrode tailings by using a cooled crusher to obtain electrode tailing powder; (2) doping the electrode tailing powder into the fibrillated material, and uniformly mixing in a mixing machine to obtain a mixed material; based on the total mass of the electrode tailing powder and the fibrillated material, the doping mass ratio of the electrode tailing powder is 0.1-10%; 3) rolling the mixed material into a film to obtain an electrode film; and 4) coating the current collector with the primer, and thermally compounding the electrode film on the current collector through a double-roller machine to obtain the dry-method electrode. According to the method, the self-supporting membrane waste generated in the membrane manufacturing and composite electrode machining process is effectively and repeatedly utilized, the production cost of the dry-method electrode is greatly saved, and compared with a dry-method electrode prepared from a pure fibril material, the specific capacity difference of the prepared dry-method electrode is within 5%, and the electrochemical performance has good consistency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical energy storage, and in particular to a method for preparing a dry electrode, which is a method for preparing a dry electrode for a lithium ion battery and a supercapacitor. Background Art

[0002] Lithium-ion batteries and supercapacitors play a vital role in new energy vehicles, portable electronic devices, and large-scale energy storage. In the electrode manufacturing process of lithium-ion batteries and supercapacitors, electrode active materials, conductive additives, binders, and solvents need to be mixed to form electrodes. Dry electrode technology is an emerging electrode manufacturing method that does not require solvents, high-energy drying equipment, and N-methylpyrrolidone (NMP) recovery equipment. At the same time, it has low equipment investment, low energy consumption, and a small required site area. The prepared dry electrode has the advantages of high surface density, excellent rate and cycle performance, and low internal resistance. The dry electrode process specifically refers to the addition of polytetrafluoroethylene (PTFE) binder after the electrode active material and conductive additive powder are evenly mixed, and the powder forms fibrillated agglomerates after mixing and strong shearing force. The block structure is extruded or rolled into a self-supporting film, and the self-supporting film is loaded onto the current collector between two rollers to form an electrode sheet. However, during the film making and composite electrode processing, the self-supporting film needs to be cut and trimmed, resulting in 20% to 30% dry electrode tailings, causing a large waste of materials and increasing the production cost of dry electrodes. Summary of the invention

[0003] In order to solve the above technical problems, the purpose of the present invention is to provide a method for preparing a dry electrode.

[0004] The present invention adopts the following technical solutions:

[0005] A method for preparing a dry electrode comprises the following steps:

[0006] 1) Low temperature pulverization: Use a cooling pulverizer to pulverize the electrode tail material to obtain electrode tail material powder. The operating temperature of the pulverizer is 0~25℃, preferably 4~8℃, and the cooling medium is water or coolant or industrial refrigeration brine. The speed of the pulverizer is 1~1000 rpm, preferably 100~300 rpm, for example 150 rpm. The particle size of the electrode tail material powder is controlled to be 10~300 mesh (10 mesh corresponds to 2mm, 300 mesh corresponds to ), preferably 16~80 mesh ( ).

[0007] 2) Add the electrode tail powder to the fibrillated material and mix them evenly in a low-speed mixer to obtain a mixed material. Based on the total mass of the electrode tail powder and the fibrillated material, the electrode tail powder is added in an amount of 0.1% to 10% by mass, preferably 0.5% to 5% by mass. The speed of the low-speed mixer is set to 1 to 1000 rpm, preferably 100 to 300 rpm.

[0008] Furthermore, in step 1), the electrode tail material comes from the dry electrode tail material generated by cutting and trimming the self-supporting film during the electrode processing.

[0009] Furthermore, the fibrillated material refers to: electrode active material, conductive additive powder and polytetrafluoroethylene binder as raw materials, the raw materials form agglomerates after mixing and shearing, and the shearing force turns the polytetrafluoroethylene microbeads into fibrils and forms a matrix, thereby mixing and supporting the electrode powder together.

[0010] In the present invention, the composition of the electrode tail powder and the fibrillated material is consistent, including electrode active material, conductive additive powder and binder, the mass percentage of electrode active material is 80%~96% (for example, 82%, 85%, 90% or 95%), the mass percentage of conductive additive powder is 2%~10% (for example, 4%, 6% or 8%), and the mass percentage of binder is 2%~10% (for example, 4%, 6% or 8%). The electrode active material is activated carbon, lithium iron phosphate, graphite, hard carbon, soft carbon; the conductive additive is conductive carbon black, conductive graphite, carbon nanotubes or a mixture thereof, such as conductive carbon black and conductive graphite mixed in a ratio of 1:1, or conductive carbon black and carbon nanotubes mixed in a ratio of 1:1. The binder is polytetrafluoroethylene.

[0011] Fibrillated materials refer to: after the electrode active material and conductive additive powder are evenly mixed, polytetrafluoroethylene (PTFE) binder is added to it, and the powder forms agglomerates after mixing and strong shearing force. The strong shearing force turns the polytetrafluoroethylene microbeads into fibrils and forms a matrix, thereby mixing and supporting the electrode powder together. This process is called binder fibrillation.

[0012] 3) Rolling the mixed material into a film at a temperature of room temperature to 120° C., preferably 60 to 80° C., to obtain an electrode film.

[0013] 4) After the primer is applied to the current collector, the electrode film is thermally composited to the current collector by a roll-to-roll machine, and the thermal composite temperature is 100-160° C., preferably 120-150° C. Automatic unwinding and automatic winding devices can be used to realize roll-to-roll preparation of dry electrodes.

[0014] The theoretical basis is that the viscosity of the primer increases rapidly above 100°C, which is not conducive to rolling and thinning processing. When the temperature is above 60°C, the bond chain of polytetrafluoroethylene opens and the viscosity increases, while the processing performance is poor when the temperature is too low. However, at low temperature, it is beneficial to crush the dry electrode tailings into smaller particles.

[0015] Beneficial effects:

[0016] The technical solution provided by the present invention can effectively reuse the self-supporting film waste generated in the process of film making and composite electrode processing, greatly saving the production cost of dry electrodes. Compared with the dry electrodes prepared from pure original fibrillated materials, the specific capacity difference of the prepared dry electrodes is within 5%, and the electrochemical performance has good consistency. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The figure is a schematic diagram of a process for preparing a dry electrode;

[0018] Figure 2 The dry activated carbon electrode tailings after crushing, see Example 2;

[0019] Figure 3 For a dry activated carbon electrode, see Example 3. DETAILED DESCRIPTION

[0020] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.

[0021] like Figure 1 As shown, a method for preparing a dry electrode comprises the following steps:

[0022] A method for preparing a dry electrode, comprising:

[0023] 1) Low temperature pulverization: Use a cooling mill to pulverize the electrode tail material at low temperature to obtain electrode tail material powder. The operating temperature of the pulverizer is 0~25℃, preferably 4~8℃, and the cooling medium is water or coolant or industrial refrigeration brine. The speed of the pulverizer is 1~1000 rpm, preferably 100~300 rpm. The particle size of the electrode tail material powder is controlled to be 10~300 mesh (10 mesh corresponds to 2mm, 300 mesh corresponds to ), preferably 16~80 mesh ( ).

[0024] 2) Add the electrode tail powder to the fibrillated material, mix them evenly in a low-speed mixer to obtain a mixed material. Based on the total mass of the electrode tail powder and the fibrillated material, the electrode tail powder is added in a mass ratio of 0.1% to 10%, preferably 0.5% to 5%. The speed of the low-speed mixer is set to 1 to 1000 rpm, preferably 100 to 300 rpm. The fibrillated material refers to: after the electrode active material and the conductive additive powder are evenly mixed, polytetrafluoroethylene (PTFE) binder is added thereto, and the powder forms agglomerates after mixing and strong shearing force. The strong shear force turns the polytetrafluoroethylene microbeads into fibrils and forms a matrix, thereby mixing and supporting the electrode powder together. This process is called binder fibrillation.

[0025] 3) Roll the mixed material into a film at a temperature of room temperature to 120°C, preferably 60 to 80°C, to obtain an electrode film. The theoretical basis is that the viscosity of the primer increases rapidly above 100°C, which is not conducive to rolling and thinning processing; the bond chain of polytetrafluoroethylene opens at a temperature above 60°C, the viscosity increases, and the processing performance is poor when the temperature is too low. Similarly, the electrode tail material is most suitable for crushing in the temperature range of 4 to 8°C, and it will not agglomerate, and the particle size of the electrode tail material powder can be controlled more accurately.

[0026] 4) After coating the primer on the current collector, the electrode film is thermally composited to the current collector by a roller machine to obtain a dry electrode. The thermal composite temperature is 100-160°C, preferably 120-150°C. Automatic unwinding and automatic winding devices can be used to realize roll-to-roll preparation of dry electrodes.

[0027] Example 1

[0028] Activated carbon (Kuraray YP50F), conductive carbon black (Super P Li from Swiss Yiruishi Company) and polytetrafluoroethylene (Shenzhen Kejing, MSK-PTFE 601X, the same below) were mixed in a mixer at a mass ratio of 80:1:1, put into a ball mill and ball milled at a speed of 300 rpm for 15 minutes, and the mixture was fibrillated to obtain a marshmallow-like mixture, thereby obtaining a fibrillated material P.

[0029] Example 2

[0030] The fibrillated material P obtained in Example 1 was repeatedly rolled by a film rolling machine to obtain a self-supporting activated carbon electrode membrane with a thickness of 120 microns. After the self-supporting activated carbon electrode membrane was trimmed and trimmed as necessary, an activated carbon electrode membrane with a specified width and a dry electrode tail were obtained. The self-supporting activated carbon electrode membrane was thermally compounded with aluminum foil at 120°C to obtain a dry activated carbon electrode A.

[0031] The dry activated carbon electrode A and 200 micron thick lithium foil were assembled into a 2032 button cell. The electrolyte was composed of 1 mol / L organic electrolyte prepared by dissolving lithium hexafluorophosphate in a mixed solvent of ethylene carbonate, diethyl carbonate and dimethyl carbonate. The volume ratio of the three solvents was 1:1:1. The button cell was charged and discharged at 0.5C current in the range of 2.0~4.0V. The specific capacity of the dry activated carbon electrode A was 62mAh / g.

[0032] Example 3

[0033] The dry electrode tail obtained in Example 2 was crushed by a low-temperature crusher, and the inner chamber of the crusher was cooled by a cooling jacket. The temperature of the cooling medium was controlled to be 5°C, and the cooling medium was water. The speed of the crusher was set to 150 rpm, so that the obtained powder could pass through a 16-mesh sieve, that is, the particle size of the particles was less than 1 mm (such as Figure 2 As shown). The obtained powder was evenly mixed with the fibrillated material P of Example 1, and the mass proportion of the obtained powder was 5% (based on the total mass of the obtained powder and the fibrillated material P of Example 1). The speed of the low-speed mixer used was set to 150 rpm. The mixed material was rolled into a 120-micron-thick self-supporting dry electrode membrane at a temperature of 60°C. After coating a primer (Shenzhen Kejing, MS-YQ-M-G813, the same below) on the microporous aluminum foil current collector, the electrode membrane was roll-to-roll hot-compounded onto the current collector at a rate of 10 m / min at 150°C by a double-roll machine to prepare a dry activated carbon electrode B, as shown Figure 3 shown.

[0034] The dry activated carbon electrode B was assembled with a lithium foil with a thickness of 200 microns into a 2032 button cell. The electrolyte was composed of a 1 mol / L organic electrolyte prepared by dissolving lithium hexafluorophosphate in a mixed solvent of ethylene carbonate, diethyl carbonate and dimethyl carbonate. The volume ratio of the three solvents was 1:1:1. The button cell was charged and discharged at a current of 0.5C in the range of 2.0~4.0V. The specific capacity of the dry activated carbon electrode B was 60mAh / g, which was not much different from the specific capacity of the dry activated carbon electrode A, and the difference was within 5%.

[0035] Example 4

[0036] A mixer was used to mix hard carbon material (GHC-C300A, Guoke Tanmei), conductive carbon black (Super P Li, Yiruishi) and polytetrafluoroethylene (MSK-PTFE 601X, Shenzhen Kejing) in a mass ratio of 85:8:7, and the mixture was put into a ball mill for ball milling at a speed of 100 rpm to fibrillate the mixture to obtain a fibrillated material.

[0037] The obtained fibrillated material is repeatedly rolled by a film rolling machine to obtain a self-supporting hard carbon electrode film with a thickness of 80 microns. After the self-supporting hard carbon electrode film is trimmed and trimmed as necessary, a hard carbon electrode film with a specified width and a dry electrode tail material are obtained.

[0038] The dry electrode tailings were crushed with a low-temperature pulverizer, and the inner chamber of the pulverizer was cooled by a cooling jacket. The temperature of the cooling medium was controlled at 4°C, and the cooling medium was industrial refrigeration brine. The speed of the pulverizer was set to 100 rpm so that the obtained powder could pass through a 16-mesh sieve, that is, the particle size of the particles was less than 1 mm. The obtained powder was mixed evenly with the fibrillated material, and the mass proportion of the obtained powder was 10% (based on the total mass of the obtained powder and the fibrillated material). The speed of the low-speed mixer used was set to 150 rpm. The mixed material was rolled into a self-supporting dry electrode film (film thickness 80 microns) at a temperature of 60°C. After coating the primer on the microporous copper current collector, the electrode film was rolled to the current collector at a rate of 10 m / min by a roller machine at 120°C to prepare a dry hard carbon electrode.

[0039] The dry hard carbon electrode and the lithium foil with a thickness of 200 microns were assembled into a 2032 button cell. The electrolyte was composed of a 1 mol / L organic electrolyte prepared by dissolving lithium hexafluorophosphate in a mixed solvent of ethylene carbonate, diethyl carbonate and dimethyl carbonate. The volume ratio of the three solvents was 1:1:1. The button cell was charged and discharged in the range of 3.0~0.005V at a current of 0.1C. The specific capacity of the dry hard carbon electrode was 350mAh / g.

[0040] Example 5

[0041] A mixer was used to mix 96% by mass of lithium iron phosphate (P98-DF5, Shenzhen Kejing) with 2% by mass of conductive additive powder (a mixed conductive agent of conductive carbon black and carbon nanotubes, provided by Liyang Liquan Technology Co., Ltd.) and 2% by mass of polytetrafluoroethylene (MSK-PTFE 601X, Shenzhen Kejing), and the mixture was put into a ball mill for ball milling at a speed of 100 rpm to fibrillate the mixture to obtain a fibrillated material.

[0042] The obtained fibrillated material is repeatedly rolled by a film rolling machine to obtain a self-supporting lithium iron phosphate electrode film with a thickness of 100 microns. After the self-supporting lithium iron phosphate electrode film is trimmed and trimmed as necessary, a lithium iron phosphate electrode film with a specified width and a dry electrode tail material are obtained.

[0043] The tailings of dry-process lithium iron phosphate electrodes with the same formula were crushed in a low-temperature pulverizer, and the inner chamber of the pulverizer was cooled by a cooling jacket. The temperature of the cooling medium was controlled at 8°C, and the cooling medium was water. The speed of the pulverizer was set to 1000 rpm, so that the obtained powder could pass through an 80-mesh sieve, that is, the particle size of the particles was less than . The obtained powder was mixed evenly with the fibrillated material, and the mass proportion of the obtained powder was 10% (based on the total mass of the obtained powder and the fibrillated material). The speed of the low-speed mixer used was set to 300 rpm. The mixed material was rolled into a self-supporting dry electrode film (film thickness 100 microns) at a temperature of 60°C. After coating the primer on the corroded aluminum foil current collector, the electrode film was thermally composited to the current collector at 150°C by a double-roller machine to prepare a dry lithium iron phosphate electrode.

[0044] The dry-process lithium iron phosphate electrode and a lithium foil with a thickness of 200 microns were assembled into a 2032 button cell. The electrolyte was composed of a 1 mol / L organic electrolyte made by dissolving lithium hexafluorophosphate in a mixed solvent of ethylene carbonate, diethyl carbonate and dimethyl carbonate. The volume ratio of the three solvents was 1:1:1. The button cell was charged and discharged at a current of 0.1C in the range of 2.5~3.6V. The specific capacity of the dry-process lithium iron phosphate electrode was 155mAh / g, which is close to the theoretical capacity (≥150mAh / g).

Claims

1. A method for preparing a dry electrode, characterized in that: The following steps are involved: 1) Use a cooling mill to crush the electrode tailings to obtain electrode tailing powder; 2) Add the electrode tail powder to the fibrillated material, mix them evenly in a mixer to obtain a mixed material; the electrode tail powder is added in a mass ratio of 0.1% to 10% based on the total mass of the electrode tail powder and the fibrillated material; 3) Rolling the mixed material into a film to obtain an electrode film; 4) After coating the primer on the current collector, the electrode film is thermally composited onto the current collector through a double-roll machine to obtain a dry electrode.

2. The method according to claim 1, characterized in that In step 1), the operating temperature of the pulverizer is 0-25° C., and the rotation speed of the pulverizer is 1-1000 rpm.

3. The method according to claim 1, characterized in that In step 1), the particle size of the electrode tail powder is 10-300 mesh.

4. The method according to claim 1, characterized in that: In step 2), the mixer speed is set to 1-1000 rpm.

5. The method according to claim 1, characterized in that In step 2), the composition of the electrode tail powder and the fibrillated material is consistent; the electrode tail powder contains electrode active material, conductive additive powder and binder. Based on the total mass of the electrode tail powder, the mass percentage of the electrode active material is 80%~96%, the mass percentage of the conductive additive powder is 2%~10%, and the mass percentage of the binder is 2%~10%.

6. The method according to claim 5, characterized in that In step 2), the electrode active material is one or more of activated carbon, lithium iron phosphate, graphite, hard carbon and soft carbon.

7. The method according to claim 5, characterized in that In step 2), the conductive additive is conductive carbon black, conductive graphite, carbon nanotubes or a mixture thereof.

8. The method according to claim 5, characterized in that In step 2), the conductive additive is a mixture of conductive carbon black and conductive graphite in a mass ratio of 1:1, or a mixture of conductive carbon black and carbon nanotubes in a mass ratio of 1:

1.

9. The method according to claim 1, characterized in that: In step 3), the temperature of the roller pressing is room temperature to 120°C.

10. The method according to claim 1, characterized in that In step 4), the temperature of thermal compounding is 100-160°C.